Political Culture and Monopoly Price Determination - Gil S. Epstein; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this paper we study the endogenous determination of monopoly price. Our proposed game of endogenous monopoly-price setting extends the literature on monopoly-price, monopoly rent-seeking contests and monopoly rent-seeking rent-avoidance contests by (i) determining the monopoly price such that it maximizes a composite utility function that depends on two components: expected social welfare and lobbying efforts. The welfare component has a positive or no effect on the utility while the lobbying efforts have a positive, negative or no effect on the utility (ii) introducing the political culture of the government and clarifying its role in the endogenous determination of monopoly price. In the proposed model the single parameter representing political culture is the weight assigned to the enhancement of social welfare. Our main concern is with the study of the relationship between this parameter and the proposed monopoly price and, in turn, the rent-seeking rent-avoidance efforts of the potential monopoly and the consumers and their aggregate expected benefit.
Keywords: 330